2009
DOI: 10.5194/angeo-27-329-2009
|View full text |Cite
|
Sign up to set email alerts
|

Quiet time F2-layer disturbances: seasonal variations of the occurrence in the daytime sector

Abstract: Abstract. Earlier revealed seasonal/latitudinal variations of the occurrence for positive and negative F2-layer Qdisturbances have been interpreted in the framework of the present-day concept of the thermosphere-ionosphere interaction. The basic process is the solar-driven and storminduced thermospheric circulation's interaction which varies with season and latitude. Such morphological features as clustering of negative Q-disturbances around winter solstice and the appearance of an additional occurrence of sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…Of course, during the night, recombination naturally causes such a depletion. However, it is well established that during times of low geomagnetic activity, the density within the ionosphere can fluctuate substantially, between about 25% and 40% on scales of a few hours to several days [Forbes et al, 2000;Mikhailov et al, 2007Mikhailov et al, , 2009. It may be that during our VLA observations, larger than average nighttime depletions occurred as a result of quiet time variability caused by forcing from the lower atmosphere via planetary waves, gravity waves, and/or tides [Chen, 1992;Rishbeth and Medillo, 2001;Liu et al, 2010].…”
Section: Discussionmentioning
confidence: 82%
“…Of course, during the night, recombination naturally causes such a depletion. However, it is well established that during times of low geomagnetic activity, the density within the ionosphere can fluctuate substantially, between about 25% and 40% on scales of a few hours to several days [Forbes et al, 2000;Mikhailov et al, 2007Mikhailov et al, , 2009. It may be that during our VLA observations, larger than average nighttime depletions occurred as a result of quiet time variability caused by forcing from the lower atmosphere via planetary waves, gravity waves, and/or tides [Chen, 1992;Rishbeth and Medillo, 2001;Liu et al, 2010].…”
Section: Discussionmentioning
confidence: 82%
“…For the meteorological influences, Mendillo et al (1998) tried to estimate to what degree the F-layer variability could be attributed to the troposphere and lower stratosphere by using the NCAR (National Center for Atmospheric Research) coupled CCM3/TIME-GCM (Community Climate Model-3/Thermospere-IonosphereMesosphere-Electrodynamics General Circulation Model; Roble and Ridley, 1994). Mikhailov et al (2007Mikhailov et al ( , 2009 showed that synchronous variation of electron density can be observed during geomagnetic quiet day in both E-and F-region. Such variability is considered to be caused by perturbation originating from lower atmosphere.…”
Section: Description Of the Similar-parameters Interpolation Methodsmentioning
confidence: 99%
“…The initial phase is observed to be recorded with an intense ionospheric storm despite the low geomagnetic storm activity at the period. This follows the fact that the variations of F2 layer quite disturbances have different formation mechanism and have been interpreted to the concept of thermosphere-ionosphere interaction (Mikhailov et al 2009). …”
Section: Resultsmentioning
confidence: 96%